Pengaruh Aktivitas Komite Audit Dan Kepemilikan Institusional Terhadap Biaya Audit - Yoma, Fransiska Dian Putri Nike; Kusmawati, Kusmawati (Jurnal Informasi Akuntansi (JIA), 2022)
This study aims to determine the effect of audit committee activity and institutional ownership on audit costs by focusing on manufacturing companies listed on the Indonesia Stock Exchange for the period 2017 - 2019. The data used are secondary data. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange. The sampling technique used was purposive sampling method and obtained 40 companies with a total of 120 samples. Hypothesis testing is done by using multiple linear regression analysis. The results of this study indicate that audit committee activity has an effect on audit costs and institutional ownership has no effect on audit costs.